Error Source Analysis and Precision Assessment of Limit Equilibrium Methods for Rock Slopes. (29th October 2018) - An, Xiaofan; Li, Ning; Zhang, Peng; Sun, Wenbo
Abstract : The approximate assumptions of limit equilibrium methods are the fundamental cause of the deviation between their calculation results and actual situation. This study proposes a new finite-element evaluation method to reflect the progressive failure characteristics of rock slopes. By comparing the results of limit equilibrium and finite-element methods, the influence factors of stability for planar landslides are systematically studied. The factors include the plastic parameters of sliding surfaces in progressive failure, the elastic parameters of sliding mass, the elastic deformation of sliding beds, and excavation stress release. Moreover, the stress distribution rules on sliding surfaces and the diversity of safety factors are explored. Finally, the error source and calculation accuracy of the limit equilibrium method in slope analysis are obtained. The study provides scientific references for analyzing and evaluating the stability of such slopes.